Perbandingan Kualitas Hidup Berdasarkan Status Gizi Pada Remaja - Susmiati; Ilfa Khairina; Hanni Oktavia Rahayu (NERS Jurnal Keperawatan)
The problem of nutritional status in the world is increasing every year. In Indonesia, the proportion of obesity in adults increased from 14.8% in 2013 to 21.8% in 2018. Adolescents which is grow with obese have a poor quality of life. such as frustration, worries, worries, and worries. The purpose of this study was to study the goals of quality of life on various nutritional statuses in adolescents. This study used a cross sectional study design. The sample of this study was all students of class XI and XII of one of Senior High School in Padang, 245 students and samples using proportional stratified random sampling technique. This study used a General Score version of the Pediatric Quality Of Life Inventory (PedsQL) questionnaire and a data sheet to determine the classification of the Body Mass Index. The prevalence of abnormal nutritional status numbers in this study was 44.9%. The prevalence of adolescents who have a good quality of life is 140 respondents (57.1%). From the t-test the quality of adolescents with normal nutritional status was higher than adolescents with abnormal nutritional status with a value (p = 0,000). This study can prove the relationship between nutritional status and quality of life in adolescents. Therefore it is expected that efforts to prevent normal nutritional status are carried out by nurses to provide health education to schools.